Cross-sectional study of perceived stress, self-esteem, body image disturbance and suicidal ideation in patients of acne vulgaris - Ghorpade, Geetanjali S.; Kadam, Kranti S.; Angane, Amey Y.; Unnithan, Vishnu B. (International Journal of Research in Dermatology, 2020)
Background: Acne vulgaris is characterized by chronic inflammation of the pilosebaceous units. It has been strongly associated with social impairment among adolescents. The study aims to assess the level of perceived stress, self-esteem, body image disturbance and suicidal ideation in patients of acne vulgaris; uncover any underlying association or correlation between these and the severity of acne vulgaris and further examine the association and co-relation of body image disturbance with perceived stress and self-esteem. Methods: Cross-sectional observational study of 72 patients with acne vulgaris was undertaken by purposive sampling technique. After taking informed consent, subjects were assessed on perceived stress scale-10, Rosenberg’s self-esteem scale, appearance anxiety inventory and Columbia-suicide severity rating scale. Spearman's correlation coefficient helped to examine the correlations. Results: 31.94% patients had severe acne, 72.22% of patients had high body image disturbance. More than half the patients of acne had high level of perceived stress. Almost three quarters of the patients had low self-esteem. 5.55% patients had suicidal ideation. No significant association was seen between severity of acne with perceived stress, self-esteem, body image disturbance and suicidal ideation. Body image disturbance was significantly associated with perceived stress and self-esteem. A positive correlation between body image disturbance and perceived stress and a negative correlation between body image disturbance and self-esteem was obtained. Conclusions: All patients, irrespective of the objective severity of acne, can experience high perceived stress and low self-esteem along with body image disturbances. This warrants consultant liaison between dermatologists and psychiatrists in routine practice for psychosocial intervention.